2021
DOI: 10.3390/ani11030871
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Shock Test Is a Practical Method for Selecting Boar Ejaculates Yielding Appropriate Seminal Plasma for Post-Thawing Supplementation

Abstract: Artificial insemination (AI) with cryopreserved semen is still unreliable for extensive pig industry application. Adding seminal plasma (SP) could improve post-thawing quality, but its suitability could vary. We applied a simple cold-shock test (CST, 5 min at 0 °C) on neat semen for classifying ejaculates (n = 63) as resistant or sensitive, obtaining two SP pools (CST-resistant: SPr, sensitive: SPs). Subsequently, frozen/thawed spermatozoa from six boars were incubated (37 °C) in MR-A® extender (control), 20% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…CMA3 has been used to analyze sperm compaction in other species [52,53]. However, it was less informative in our study, in line with previous reports for pig spermatozoa [29,30,43]. A possible reason could be that this technique could help identify boars with altered spermatogenesis, whereas those used in this study were subjected to strict evaluation.…”
Section: Cma3 For the Evaluation Of Chromatin Compaction In Pig Sperm...supporting
confidence: 57%
See 4 more Smart Citations
“…CMA3 has been used to analyze sperm compaction in other species [52,53]. However, it was less informative in our study, in line with previous reports for pig spermatozoa [29,30,43]. A possible reason could be that this technique could help identify boars with altered spermatogenesis, whereas those used in this study were subjected to strict evaluation.…”
Section: Cma3 For the Evaluation Of Chromatin Compaction In Pig Sperm...supporting
confidence: 57%
“…In contrast, the influence of the SCSA or the 8-oxo-dG levels was much lower (also shown in the models' results). The ability of mBBr analysis to find differences between treatments was not evident in previous studies [29,30] but still showed good sensitivity to incubation or storage. In any case, mBBr should be tested for discrimination power among boars and to determine if it is related to stressful events or male fertility, as is the case for SDF [15,16,38,55,56].…”
Section: Multivariate Analyses Enhance Discovering Variable Associati...mentioning
confidence: 62%
See 3 more Smart Citations